ENHANCING CREATIVITY IN THE EDUCATIONAL PROCESS THROUGH PEDAGOGICAL TECHNOLOGIES - Khomidjonov Abrorjon Olimjon ugli (International Scientific and Current Research Conferences, 2025)
The present study examines the critical role of pedagogical technologies in fostering creativity within educational environments. Creativity, as a fundamental competency in the 21st century, necessitates innovative teaching approaches that transcend conventional instructional methods. Pedagogical technologies, encompassing digital tools, collaborative platforms, and adaptive learning strategies, provide structured frameworks that stimulate cognitive flexibility, problem-solving skills, and imaginative thinking among learners. This article investigates the theoretical underpinnings, practical applications, and methodological implications of integrating pedagogical technologies to cultivate creative potential in students. By analyzing contemporary research and international educational practices, the study highlights effective strategies for embedding creativity in curricula, designing interactive learning experiences, and assessing creative outcomes. The findings emphasize the transformative impact of technology-driven pedagogical interventions in enhancing learner autonomy, engagement, and intellectual curiosity.